Isolation of phages infecting the abundant freshwater Actinobacteriota order 'Ca. Nanopelagicales' - Kavagutti, Vinicius S; Chiriac, Maria-Cecilia; Ghai, Rohit; Salcher, Michaela M; Haber, Markus (The ISME journal, 2023)
Low-GC Actinobacteriota of the order 'Ca. Nanopelagicales' (also known as acI or hgcI clade) are abundant in freshwaters around the globe. Extensive predation pressure by phages has been assumed to be the reason for their high levels of microdiversity. So far, however, only a few metagenome-assembled phages have been proposed to infect them and no phages have been isolated. Taking advantage of recent advances in the cultivation of 'Ca. Nanopelagicales' we isolated a novel species of its genus 'Ca. Planktophila'. Using this isolate as bait, we cultivated the first two phages infecting this abundant bacterial order. Both genomes contained a whiB-like transcription factor and a RNA polymerase sigma-70 factor, which might aid in manipulating their host's metabolism. Both phages encoded a glycosyltransferase and one an anti-restriction protein, potential means to evade degradation of their DNA by nucleases present in the host genome. The two phage genomes shared only 6% of their genome with their closest relatives, with whom they form a previously uncultured family of actinophages within the Caudoviricetes. Read recruitment analyses against globally distributed metagenomes revealed the endemic distribution of this group of phages infecting 'Ca. Nanopelagicales'. The recruitment pattern against metagenomes from the isolation site and the modular distribution of shared genes between the two phages indicate high levels of horizontal gene transfer, likely mirroring the microdiversity of their host in the evolutionary arms race between host and phage.
Keywords: Phylogeny; Gene Transfer, Horizontal; Bacteria; genom virový; Metagenome; metagenom; Genome, Viral; sladká voda; Fresh Water; přenos genů horizontální; Bacteriophages; fylogeneze; bakteriofágy